“That we may obtain our religious liberty…”: Aboriginal Women, Faith and Rights in Early Twentieth Century Victoria, Australia* - Grimshaw, Patricia (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2008)
AbstractThe paper, focused on a few years at the end of the First World War, explores the request of a group of Aborigines in the Australian state of Victoria for freedom of religion. Given that the colony and now state of Victoria had been a stronghold of liberalism, the need for Indigenous Victorians to petition for the removal of outside restrictions on their religious beliefs or practices might seem surprising indeed. But with a Pentecostal revival in train on the mission stations to which many Aborigines were confined, members of the government agency, the Board for the Protection of the Aborigines, preferred the decorum of mainstream Protestant church services to potentially unsettling expressions of charismatic and experiential spirituality. The circumstances surrounding the revivalists’ resistance to the restriction of Aboriginal Christians’ choice of religious expression offer insight into the intersections of faith and gender within the historically created relations of power in this colonial site. Though the revival was extinguished, it stood as a notable instance of Indigenous Victorian women deploying the language of Christian human rights to assert the claims to just treatment and social justice that would characterize later successful Indigenous activism.